HUBUNGAN PERAN ORANG TUA DENGAN KEMAMPUAN TOILET TRAINING PADA ANAK USIA TODDLER DI PAUD PERMATA BUNDA RW 01 DESA JATI SELATAN 1 SIDOARJO - Devi Muji Rahayu; Firdaus S.Kep., Ns., M.Kes (Universitas Nahdlatul Ulama Surabaya, 2018)
Introduce: The events that often occurs in toddler is inability to perform the toilet training. It is because the parents are less active in their role. The purpose of this study is to know the relationship of parental role with the ability of toilet training for toddler in Permata Bunda Early childhood education at RW 01 of Jati Selatan 1 village Sidoarjo. Study design is analytic with cross-sectional approach. The population were all parents and toddler. Number of sample were 24 respondents taken by simple random sampling technique. Data were collected by questionnaire and observation. The independent variable is role of parents and the dependent variable is the ability of toddler performed toilet training. The data obtained were processed by SPSS 17.0 use chi-square test with significance level α (0.05). The results of study of role of parents indicate that a half of parents (50%) had lack of parental roles and the capabilities of toilet training for the toddler mostly (54.2%) were not able to perform toilet training. Based on chi-square test found p = 0.001 < 0.05, which means that H0 is rejected so there is relationship of parental role with the ability of toilet training for toddler. Conclusions of this study is the better role of parents, the better the ability of the child. Suggested to parents to understand the learning readiness of children in toilet training so it can maximize child learning and toilet training capabilities.